I have the following exact equations, however, teacher said it is incorrect. Cannot find a mistake. Could you please help me? (3x^2 - 2x - y) dx + (2y - x + 3y^2)dy = 0 This is exact equation, because: P = (3x^2 - 2x - y) Q = (2y - x + 3y^2) P'y = Q'x = -1 Then integrate Intx P = x^3 - x^2 - yx + fi(y). Find derivative: (x^3 - x^2 - yx + fi(y)'y = -x+ fi'(y) = Q = (2y - x + 3y^2). Find fi'(y) = 2y + 3y^2. Iegūst fi(y) = y^3 + y^2. Result: x^3 - x^2 - yx + y^3 + y^2 + C. Where is a mistake? Mabybe the whole idea is incorrect? Please, help me.